2016
DOI: 10.1242/jeb.134411
|View full text |Cite
|
Sign up to set email alerts
|

Differences in the timing of cardio-respiratory development determine whether marine gastropod embryos survive or die in hypoxia

Abstract: Physiological plasticity of early developmental stages is a key way by which organisms can survive and adapt to environmental change. We investigated developmental plasticity of aspects of the cardio-respiratory physiology of encapsulated embryos of a marine gastropod, Littorina obtusata, surviving exposure to moderate hypoxia (P O2 =8 kPa) and compared the development of these survivors with that of individuals that died before hatching. Individuals surviving hypoxia exhibited a slower rate of development and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 88 publications
(101 reference statements)
0
8
0
Order By: Relevance
“…Although our limited data set does not allow for detailed inferences about the mechanistic basis of the observed response, it does show that physiological responses to low oxygen exposure co-vary with size and life-stage. Ontogeny-related processes such as the regulation of metabolic rates (Spicer and El-Gamal 1999 ), functional changes on subunits of oxygen transport proteins (Terwilliger and Brown 1993 ; Brown and Terwilliger 1999 ) and the development of the cardiovascular system (Harper and Reiber 2006 ; Rudin-Bitterli et al 2016 ) could contribute to the variation in mass exponent in relation to oxygen tension described here. In our study, the largest life-stage (i.e.…”
Section: Discussionmentioning
confidence: 87%
“…Although our limited data set does not allow for detailed inferences about the mechanistic basis of the observed response, it does show that physiological responses to low oxygen exposure co-vary with size and life-stage. Ontogeny-related processes such as the regulation of metabolic rates (Spicer and El-Gamal 1999 ), functional changes on subunits of oxygen transport proteins (Terwilliger and Brown 1993 ; Brown and Terwilliger 1999 ) and the development of the cardiovascular system (Harper and Reiber 2006 ; Rudin-Bitterli et al 2016 ) could contribute to the variation in mass exponent in relation to oxygen tension described here. In our study, the largest life-stage (i.e.…”
Section: Discussionmentioning
confidence: 87%
“…Whilst lower than the O 2 saturation used in the present study, Chan et al (2008) reported a reduction in velum area under moderate hypoxia (57.5% air saturation) in planktotrophic Reticunassa (as Nassarius) festivus, contrasting with our results. Rudin-Bitterli et al (2016) proposed that enhanced plasticity in encapsulated developers, relative to those with planktotrophic modes of development, could arise from greater fluctuations in P O2 in the intertidal environment (Morris and Taylor, 1983). Here, planktotrophic L. littorea embryos, the focus of the present study, are shown to respond to relatively small reductions in dissolved oxygen, despite the supposed less extreme fluctuations these embryos are likely to experience in the water column (Agnew and Taylor, 1986).…”
Section: The Developmental Environmentmentioning
confidence: 62%
“…Comparisons of embryos that hatched and those that died There were pre-hatch mortalities in all treatments (N-H: 6; H-H: 10; H-N: 5; N-N: 4), and so the opportunity was taken to compare embryos that successfully hatched with those that died to identify traits linked with successful hatching (see also Rudin-Bitterli et al, 2016). By presenting data for comparisons of those that successfully hatched and those that died, inferences can also be made over the selective advantages of morphological traits under mild hypoxia.…”
Section: Albumen Diameter Correlationsmentioning
confidence: 99%
See 2 more Smart Citations